639 ENT Telephone Follow Up in The Era of Covid-19: A Retrospective Qualitative Analysis Utilising Semi structured focus groups. (4th May 2021) - Keates, N; Mclaren, O; Perkins, C; Finnie, C; Williams, R
Abstract: Introduction: Covid-19 and social distancing has triggered a seismic shift in clinical work especially during the first part of lockdown. This work looks to evaluate the experience and opinions of key stakeholders who took part in the process and use this to improve follow up in the future. Method: 3 Focus groups following the same semi structured format discussed key considerations in follow up in general, telephone follow up, key aspects in its delivery and how this could benefit the service provided to patients. The focus groups involved Juniors (registrar level doctors), Consultants and support staff (clinical and non-clinical). Results: Several themes and subthemes were identified. Key points were that patients were universally in favour of telephone consultations; they find them convenient and enjoy not attending the hospital. All clinicians agreed that although Covid-19 lead us to review New patients via telephone this increased workload as they needed to attend later for an examination and felt it did not provide safe care. Conclusions: There is certainly an increasing role for telephone follow ups in the wake of Covid-19 which can benefit ongoing patient care and aid in managing the departments follow up capacity. Further work is needed to review this.